Epigraphic Programs in Almoravid Constructions: The Commemoration of The Emirs’ Supremacy - Marcos-Cobaleda, María (My University, 2018)
Despite the ideas transmitted in the traditional historiography, during the Almoravid period, the arts –especially the architecture- had a prominent place within the issues of the Empire. This fact became more important from the naissance of the Almohad movement during the 20’s of the 12th century. In that context, the Almoravid emirs found in the architectural programs a direct manner to shape their political and religious ideas against the Unitarians and to spread them across their territory. Within this framework, the aim of this paper is to analyze the outstanding role of the epigraphic programs in Almoravid constructions, in one hand as a differentiating element from the Almohads (both in content and form) and, on the other hand, as a way to focus on the Almoravid political and religious supremacy and the impregnation of these ideas in the collective memory. To achieve this aim, we will study the epigraphic programs of the main Almoravid artistic manifestations (including the Almoravid Friday mosques and their minbars) and we will compare their content and form with other Islamic manifestations in East and West. Moreover, we will analyze these epigraphic programs in the general context where they are included, as an important part of the conformation of the Almoravid aesthetic. Due to the fact that the Almoravids are considered the introducers of the cursive epigraphy in the West throughout its use at the Qubbat al-Bārūdiyyīn in Marrakech, we will compare the wide spread (both temporary and geographically) of this type of calligraphy with the case of other artistic elements highly developed by them. Therefore, we can conclude that the Almoravid emirs had an important role as renovators of the Western Islamic artistic programs, which they used both as a way of commemoration and as symbol of their political and religious ideas.
Keywords: Al-Andalus - Historia - 1086-1143 (Almorávides); Almoravids; 12th Century; Al-Andalus; North Africa; Epigraphy